Keabsahan Pendaftaran Kapal sebagai Objek Jaminan Hipotek - Lina Kamilah Tsani; Nynda Fatmawati O. (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Mortgages with collateral as collateral for ships are one of the credit agreements that support business activities in the current era of globalization and free trade. Ship mortgages can of course also support business activities in Indonesia because it is an archipelagic country which, when distributing goods between one island and another, uses ship transportation facilities. However, in Indonesia there is no separate law that regulates mortgage guarantees, so legal protection for creditors is very lacking because the mortgage regulations in BW are in practice less relevant for the increasingly rapid development of the business world. In particular, legal protection regarding the execution of mortgage guarantees if the debtor defaults is deemed to be very lacking. Therefore, the Notary as an official authorized to make a mortgage deed must truly understand his duties in order to achieve justice and legal protection for the parties contained in the mortgage agreement deed.